THE GUIDELINES FOR PARTICIPATORY ACADEMIC ADMINISTRATOR BASED-ON APARIHANIYADHAMMA 7 OF PRIMARY SCHOOL SMAIL SIZE SCHOOL UNDER NAKHON SAWAN PRIMARY SCHOOL EDUCATION SERVICE AREA 1 - Intarawiset, Chayanat; Uttaro, Phramaha Udorn; PhrakhruSrisuthamniwit (Journal of Educational Review Faculty of Education in MCU, 2024)
This research article aimed 1) to study the state of participatory academic administration of small school administrators and 2) to create a guideline for participatory academic administration of administrators based on the 7 principles of Aparihniyadhamma in small schools. A mixed-method research was used. The quantitative research collected data from 286 samples. The research instrument was a questionnaire with a reliability of 0.94. Data were analyzed by finding frequency, percentage, mean, and standard deviation. The qualitative research used a semi-structured interview method by collecting data from 9 key informants and analyzing the data by content analysis. The research results showed that 1) the state of participatory academic administration of small school administrators was at a high level overall and 2) the guideline for participatory academic administration of administrators based on the 7 principles of Aparihniyadhamma in small schools was as following: (1) Curriculum administration: administrators should organize a system for formulating the school curriculum that allowed all parties to participate in the development. (2) Teaching and learning management: administrators should organize a system for developing the learning process continuously, allowing learners to interact socially with individuals and various sources of knowledge. (3) Development of innovative media and educational technology. Administrators promoted teachers to produce and develop teaching media and innovations, and cooperate with government and private agencies to promote development. (4) Measurement and evaluation: Administrators supervise and monitor measurement and evaluation, academic administration, and were open and straightforward. Administrators should organize workshops to create and develop tools and conduct evaluations that covered all learning subject groups. (5) Supervision within the educational institution: Administrators planed for all parties to participate in recognizing the criteria and practices to support educational supervision. (6) Development of an internal quality assurance system in the educational institution: Administrators set additional educational standards of the educational institution to be consistent with national educational standards, basic education standards, and standards of the Office of the Basic Education Commission.